2022
DOI: 10.3389/fbioe.2022.906704
|View full text |Cite
|
Sign up to set email alerts
|

Methane Single Cell Protein: Potential to Secure a Global Protein Supply Against Catastrophic Food Shocks

Abstract: Global catastrophes such as a supervolcanic eruption, asteroid impact, or nuclear winter could cause global agricultural collapse due to reduced sunlight reaching the Earth’s surface. The human civilization’s food production system is unprepared to respond to such events, but methane single cell protein (SCP) could be a key part of the solution. Current preparedness centers around food stockpiling, an excessively expensive solution given that an abrupt sunlight reduction scenario (ASRS) could hamper convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 82 publications
(121 reference statements)
0
19
0
Order By: Relevance
“…García Martínez et al, 2022Martínez et al, , 2021 was selected for being the current higher TRL example of MP production. It consists rst in a hollow-ber ultra ltration system to concentrate the broth with reduced energy requirements.…”
Section: Microbial Proteins Production From Residual-based Gases: For...mentioning
confidence: 99%
“…García Martínez et al, 2022Martínez et al, , 2021 was selected for being the current higher TRL example of MP production. It consists rst in a hollow-ber ultra ltration system to concentrate the broth with reduced energy requirements.…”
Section: Microbial Proteins Production From Residual-based Gases: For...mentioning
confidence: 99%
“…Research has described a range of resilient foods (Tzachor et al., 2021; Winstead & Jacobson, 2022), especially for abrupt sunlight reduction scenarios (Denkenberger & Pearce, 2015; Denkenberger et al., 2019). Resilient food solutions include leaf protein concentrate (J. M. Pearce et al., 2019), greenhouse crop production (Alvarado et al., 2020), single cell protein from natural gas (García Martínez, Pearce, et al., 2022) and hydrogen (García Martínez et al., 2021), sugar from lignocellulosic biomass (Throup et al., 2022), synthetic fat from petroleum (García Martínez, Alvarado, & Denkenberger, 2022), and wild edible plants (Winstead & Jacobson, 2022). One modeling study concluded that these resilient foods could provide enough calories to avoid anyone starving after the nuclear war scenario (Rivers et al., 2022).…”
Section: Why Seaweed?mentioning
confidence: 99%
“…It was estimated that a 1 m 3 unit will require 0.7 kg cell biomass and can enable methane mitigation at the rate 6 kg CH 4 /d. Considering that methanotrophic cell biomass can be produced at the cost $1.7-5/kg [19,20], the system may offer an attractive mitigation platform and, thus, it was investigated further.…”
Section: Mathematical Modelmentioning
confidence: 99%